Kaninhållning för sällskapsbruk - Edbom, Marie (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
The domesticated rabbit stems from the European Wild rabbit and researchers have found that they share most of the characteristics and behaviors of their wild ancestor. They form mating groups in which strong hierarchic orders are formed and they are known for their ability to dig warrens which serve as one of the most important resources for this species. Although research has been performed to increase the welfare of rabbits kept in laboratory settings little is known about the housing, behavior and welfare of the pet rabbit. Among the research that has been performed within the area results have shown that the animals are kept in small solitary cages and that although many rabbits are purchased mainly for the children many animals cannot be handled by children due to display of aggression. Another conclusion drawn is that the animals are kept in ways that differs greatly from their natural environment. The current study hence served to investigate more about the housing and behavior of pet rabbits in Swedish households. Data was collected through a survey made available online via the website of Sweden’s University of Agriculture. The survey was also handed out through the help of one pet store in each county of Sweden. Each pet store was assigned 15 questionnaires. A total of 189 people partook in the internet survey and 41 in the survey handed out via the pet stores. The results show that the rabbits in the study are kept in larger enclosures than those found in previous literature and that most rabbits are kept outdoors throughout the year. Furthermore, the results show that most animals are kept in solitary housing which concurs with previous literature, and that only a small portion of animals kept in group or pair housing get access to more than one resource per individual. In spite of this the amount of aggressive interactions as well as abnormal behaviors found is relatively low. A discussion is carried out to further investigate possible correlations between environmental factors and behaviors. A conclusion drawn from the results is that more research needs to be done in this area to get more insight in the welfare of pet rabbits in Swedish households. Of interest would also be further studies on links between behavior and housing systems as well as differences in housing between pet owners answering via internet and via pet stores. Interest to partition in the study shown by pet owners also provides room for further research in this area of need.